Factors Affecting Work Life Balance among Administrator in a Public University during COVID-19 - Idaya Husna Mohd; Abd Kadir Othman; Nor Haslinda Desa; Mohd Hafizi Zambry (Information Management and Business Review, 2023)
This study is conducted to examine the relationship between job stress, supervisor support and work attitudes toward work-life balance during Covid-19 among employees in an administration office at a Public University in Selangor. The independent variables of this study consist of job stress, supervisor support, and work attitude; whereas the dependent variable in this study is work-life balance. The quantitative research method is selected and a questionnaire is used as the research instrument to collect data. There are 110 samples selected from the Administration office (N=110). The data collected is analyzed by using Statistical Packages for Social Science Version 26.0 (SPSS Version 26.0) software. Data was then analyzed both descriptively and inferentially. The results revealed that all variables have a significant positive relationship between supervisor support and work attitude with work-life balance and a significant negative relationship between job stress and work-life balance. The study emphasized the need for organizations to review the relevance of work-life balance programs, policies and activities that support and encourage employees to reduce stress in a workplace. Supervisor support also has the impact of making a positive work attitude among employees. This study gives insight to the organization in designing an appropriate system to enhance work-life balance.